Dad - Robinson, Christian (Balzer + Bray, 2026)
Dad is strong. Dad is sweet. Dad is here now. Dad had to go away. There are as many ways to be a dad as there are dads in the world. Dad is a bighearted tribute to all of them, reflecting the range of relationships dads have with their little ones.